Integrated implosion/heating studies for advanced fast ignition - Norreys, P; Lancaster, K; Murphy, C; Habara, H; Karsch, S; Clarke, R; Collier, J; Heathcote, R; Hemandez-Gomez, C; Hawkes, S; Neely, D; Hutchinson, M; et al. (2004)
The ultrafast heating of implosions using cone/shell geometeries was discussed. The study was carried out by using the 1054 nm, nanosecond, 0.9 kJ output of the VULCAN Nd:glass laser to drive 186 μm diameter, 6 μm wall thickness Cu-dopped deuterated plastic (CD) shells in 6-beam cubic symmetry. It was found that x-ray preheat, combined with lower ablation pressures, indicate that infrared drive was unlikely to be useful in full scale direct drive ignition design. The results show that the higher density of the compressed plasma promotes more collimated flow, but at the cost of reduced background heating.